Making a #Stepchange? Investigating the Alignment of Learning Analytics and Student Wellbeing in United Kingdom Higher Education Institutions - Ahern, Samantha J. (Frontiers in Education, 2020)
In recent years there has been growing concern around student wellbeing and in particular student mental health. Numerous newspaper articles (Ferguson 2017; Shackle 2019) have been published on the topic and a BBC 3 documentary (‘BBC Three - Death on Campus: Our Stories’ n.d.) was produced on the topic of student suicide. These have coincided with a number of UK Higher Education sector initiatives and reports, the highest profile of these being the Universities UK ‘#StepChange’ report (Universities UK 2017) and the Institute for Public Policy Research ‘Not By Degrees’ report (‘Not by Degrees: Improving Student Mental Health in the UK’s Universities’ 2017). Simultaneously, learning analytics has been growing as a field in the UK, with a number of institutions running services predominantly based on student retention and progression, the majority of which make use of the Jisc Learning Analytics service. The 2017 Universities UK (UUK) #StepChange report states: “Institutions are encouraged to align learning analytics to the mental health agenda to identify change in students’ behaviours and to address risks and target support.” (Universities UK, 2017). This study was undertaken in the 2018/19 academic year, a year after the launch of the #StepChange framework and after the formal transition of Jisc’s learning analytics work with partner HEIs to a national learning analytics service. This paper concludes that, although learning analytics is a growing field and becoming operationalised witin UK Higher Education it is still in its reative infancy. Current data models rely on proxies for student engagement and may not truly represent student behaviours. At this time there is inadequate sophistication for the use of learning analytics to identify student wellbeing concerns. However, as with all technologies, learning analytics is not benign, and changes to ways of working impact on both staff and students, wellbeing professionals should be included as key stakeholders in the development of learning analytics and student support policies and wellbeing considerations explicitly mentioned and taken into account.